Validation of a thermo-hydro-mechanical model of freezing of water-saturated soil based on laboratory tests results - Zhelnin, Maksim Sergeyevich; Kostina, Anastasiya Andreyevna; Prokhorov, Aleksandr Evgen’yevich; Plekhov, Oleg Anatol’yevich; Semin, Mikhail Aleksandrovich; Agutin, Kirill Alekseyevich (Computational Continuum Mechanics, 2021)
Frost heave of freezing water-saturated soils is an important worldwide problem from an engineering point of view. In cold regions, this phenomenon significantly affects foundations of buildings and road pavements. Application of artificial ground freezing to underground construction due to frost heave can cause an undesirable uplift of the ground surface and an increase in pressure acting on a lining and frozen wall. In the present paper, a mathematical model of soil freezing enabling one to predict soil deformation due to phase transformation of pore water into ice is proposed. The model is based on a set of nonlinear equations of water transfer, heat transfer, and equilibrium which are solved relative to porosity, temperature, and displacement variables. Constitutive relations of the poromechanics theory along with Bishop-type effective stress are used to simulate the mechanical behavior of soil during the process of pore water freezing and to evaluate pore pressure depending on a changein porosity and volumetric strain. Moreover, equations of the associated flow rule of plasticity are incorporated into the model to describe an inelastic volumetric expansion of the freezing soil induced by pore ice pressure. The ability of the model to capture essential features of the freezing process of water-saturated soils is demonstrated by numerical simulation of two laboratory tests. For the first test, a comparison between results of the numerical simulation and experimental measurements of variations of temperature and uplift of the top surface of silty clay specimens with time has been conducted. It has been shown that the numerical results are highly consistent with the measurements when the soil specimen is frozen with the growth of a massive cryogenic structure. In the numerical simulation of the second test, the calculated radial deformation of freezing soil is in good agreement with the experimental measurements, obtained by a fiber-optical sensor during the radial freezing of the quartz sand sample in a closed system.
Keywords: artificial ground freezing; frost heave; numerical simulation; fiber-optic sensor